1985
DOI: 10.1520/jfs11017j
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of Buried Bodies and Methods That May Aid in Their Location

Abstract: This is the second report on an ongoing study conducted to collect data on the decompositional rates of human cadavers and the first on buried cadavers. Six unembalmed human cadavers were buried separately in unlined trenches of various depths and allowed to naturally decompose for a time period ranging from a month to a year. During the period of burial, data were collected daily on the air, soil, and cadaver temperature at each burial site. At the end of each specified burial period the cadavers were exhumed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
185
1
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(205 citation statements)
references
References 6 publications
11
185
1
6
Order By: Relevance
“…This fall in pH is in keeping with more complete decomposition at the higher temperature and is similar to findings from related research (Vass et al, 1992). The patterns of pH change observed in the absence of an enteric flora suggest that the soil microbial biomass may have contributed to the changes in pH observed in the presence of whole cadavers in other studies (Rodriguez and Bass, 1985;Vass et al, 1992;Hopkins et al, 2000).…”
Section: Discussionsupporting
confidence: 88%
“…This fall in pH is in keeping with more complete decomposition at the higher temperature and is similar to findings from related research (Vass et al, 1992). The patterns of pH change observed in the absence of an enteric flora suggest that the soil microbial biomass may have contributed to the changes in pH observed in the presence of whole cadavers in other studies (Rodriguez and Bass, 1985;Vass et al, 1992;Hopkins et al, 2000).…”
Section: Discussionsupporting
confidence: 88%
“…Advances in the understanding of gravesoils are primarily empirical observations (Illingworth 1926;Mant 1950;Evans 1963b;Morovic-Budak 1965;Sagara 1976;Micozzi 1991;Dent et al 2004) or made during the study of insect and/or scavenger activity (Bornemissza 1957;Reed 1958;Payne 1965;Rodriguez and Bass 1985;DeVault et al 2003). These observations and studies showed that introduction of cadaveric material into the soil is primarily regulated by the activity of insects and scavengers and the mass of the cadaver.…”
Section: The Formation Of Gravesoilmentioning
confidence: 99%
“…Although the majority of cadavers that die in nature are located on the soil surface, a number of studies were conducted to understand cadaver decomposition after burial in soil (Motter 1898;Mant 1950;Lundt 1964;Sagara 1976;Lötterle et al 1982;Rodriguez and Bass 1985;DeGaetano et al 1992;Child 1995;Spennemann and Franke 1995;VanLaerhoven and Anderson 1999;Hopkins et al 2000;Fiedler et al 2004;Carter 2005;Forbes et al 2005aForbes et al , 2005aWeitzel 2005;Carter and Tibbett 2006). While the results from these studies might be of little interest to the terrestrial ecologist, this aspect of below-ground ecology merits attention because it might be of significance to the archaeologist, forensic scientist, and those concerned with animal composting or the disposal of farm animals.…”
Section: Cadaver Burial and Gravesoil Ecologymentioning
confidence: 99%
See 1 more Smart Citation
“…So far, soil investigations in crime scenes have focused mainly on locating burial sites [3,4] and on the identification of soil samples recovered from suspects' footwear, clothes, vehicles or weapons [5][6][7][8][9][10]. However, a decomposing cadaver strongly modifies the soil environment and as a result affects the soil organisms [11,12].…”
Section: Introductionmentioning
confidence: 99%